Eksplorasi Potensi Kulit Vegan Berbasis Selulosa Bakteri: Sifat Material, Keberlanjutan, dan Aplikasinya - junaidi salam; Nina Maftukha; Anita Armas (Aliansi Desainer Produk Industri Indonesia (ADPII), 2026)
The film produced from nata de coco after the drying process is a thin sheet like paper so that the lamination technique is an effort to form a new performance of the material structure to become a material `like leather`. By considering the three main focuses of the structural requirements and properties of the material to be proposed (1) The effect of the number of layers and lamination arrangement patterns on the distribution of stress and tensile strain of the cellulose film sheet, (2) Form resistance, and (3) Elasticity, then the fulfillment of technical and mechanical aspects is needed when the creation of alternative leather materials is carried out by approaching the expected properties of leather materials on the product commodities that will be designed later. The focus of this research is to understand how the performance of bacterial cellulose film laminate material as vegan leather by considering three main focuses of the structural requirements and properties of the material to be proposed, and how to stimulate creative thinking in materials that motivate design through four components of experience (case study of bacterial cellulose film laminate material as vegan leather) This research was conducted with two stages of methods, where the first is a quantitative-experimental method in collecting material manufacturing data, the steps described in the initial stage are testing material samples through variable number of layers, and various technical treatments, to determine the parameters of elasticity and surface strain of the material required on the design object then the second is at the stage of designing the material or product concept with the Material Driven Design (MDD) method, The performance of this bacterial cellulose film laminate material is obtained the more layers of lamination will affect the strength of the material, and for the resistance of the form has been tested in the drying process of the material that is pressed and stretched until the surface is completely dry, while elasticity is not realized in the results of stretching the wet material to dry. The elasticity of the material is still questionable and is a proposal for further research, but from the results of the concept development based on the Vision of Material Experience and prediction of acceptance, the concept of molding vamp shoes is proposed for further development.